2011
DOI: 10.1200/jco.2011.35.9638
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcome of Patients With Non–Small-Cell Lung Cancer Harboring BRAF Mutations

Abstract: We report for the first time to our knowledge that V600E and non-V600E BRAF mutations affect different patients with NSCLC. V600E mutations are significantly associated with female sex and represent a negative prognostic factor. In addition, we identified a number of other clinicopathologic parameters potentially useful for the selection of patients carrying BRAF mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
413
4
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(472 citation statements)
references
References 33 publications
34
413
4
5
Order By: Relevance
“…BRAF p.V600E mutation is more frequent in females 52,54 and never smokers 54 in some studies, but several studies failed to show these associations. 49,50,53,58 One distinction between BRAF mutations and other Figure 1 Forest plot of sensitivity and specificity for immunohistochemistry (IHC)-based determination of ROS1 rearrangement positivity compared with fluorescence in situ hybridization.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRAF p.V600E mutation is more frequent in females 52,54 and never smokers 54 in some studies, but several studies failed to show these associations. 49,50,53,58 One distinction between BRAF mutations and other Figure 1 Forest plot of sensitivity and specificity for immunohistochemistry (IHC)-based determination of ROS1 rearrangement positivity compared with fluorescence in situ hybridization.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
“…49e52, 54 In lung cancer, data from a 2016 phase II single-arm clinical trial 56 showed that single-agent dabrafenib given in second line to stage IV BRAF p.V600E mutant NSCLC had a partial response rate of 33% and disease control rate of 58% and combination dabrafenibtrametinib therapy given in second line to stage IV BRAF p.V600E mutant lung adenocarcinoma had a partial response rate of 63% and disease control rate of 75%.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
“…Litvak, et al observed that among patients with advanced stage NSCLC harboring B-Raf mutations, those with V600 mutations had a longer 3-year overall survival rate compared with patients with non-V600 mutations (24% versus 0%; p < 0.001) (Litvak et al, 2014). On the contrary, the study published by Marchetti et al involving 1046 patents (37 harboring B-Raf mutations) found the V600E mutation as a negative prognostic factor, significantly associated with shorter overall survival on multivariate analyses (HR for death: 2.18; P = .014) (Marchetti et al, 2011).…”
Section: Mutationmentioning
confidence: 87%
“…Mutations in BRAF are seen in approximately one-half of melanomas, in which BRAF V600E is a driver mutation that can be effectively targeted with selective BRAF and/or MEK inhibitors. Mutations in BRAF are also detected in 2 to 4% of NSCLCs (27)(28)(29). The mutations found in NSCLC are distinct from the melanoma setting: whereas BRAF-mutated melanomas harbor a V600E amino acid substitution in more than 80% of cases, lung adenocarcinomas harbor non-V600E mutations in 40 to 50% of cases.…”
Section: Braf Mutationsmentioning
confidence: 95%